Chinese factor in Central Asia - Aсыл М. Б. (Journal of Oriental Studies, 2018)
In this paper the author investigate the Chinese factor in Central Asian countries. Through the prism of the geopolitical situation in Central Asia, the author evaluates the relationship of China and the RK. The author also reviewed the internal problems of China that may have an impact on China’s policy in Central Asia.